Condition of the Progo River Upstream in Temanggung Regency based on Community Structure and Saprobic Index of Plankton - Alvin Afriliandri; Riche Hariyati; Tri Retnaningsih Soeprobowati; Mirza Hanif Al Falah (Indonesian Society of Limnology, 2024)
Upstream of the Progo River in Temanggung Regency, it supports the daily lives of the surrounding community. As time goes by, human activities such as land conversion, deforestation, stone mining, agricultural activities and household waste slowly affect the condition of the waters in the Progo River, so it is necessary to monitor water quality. Plankton can indicate changes in water quality because it is responsive to changes in water quality. This research aims to assess the quality of the water environment using community structure and the saprobic index of plankton. Ten sampling stations were selected using the purposive random sampling method. Plankton were collected using a plankton net, water quality measurements were carried out using a Horiba water checker, and testing in the environmental engineering laboratory. As a result, 81 plankton species had an abundance per station of 805-3,981 ind/L. The diversity index (H') indicates a stable ecosystem, the Evenness Index (e) has a fairly even distribution, and the Dominance Index (D) is at all stations with no dominant species. According to PP No. 22 of 2021, the quality of the Progo River Upstream meets environmental quality standard criteria, except for DO and total N (class I). Based on the saprobic index and bioindicator species, it indicates that all stations belong to the ?-Mesosaprobic. Several types of plankton that can be used as bioindicators of water quality include Cladophora glomerata, Tabellaria sp., and zooplankton, which are Lecane sp.